Steatosis in chronic hepatitis B: Prevalence and correlation with biochemical, histologic, viral, and metabolic parameters - Archana Rastogi; Puja Sakhuja; Ashish Kumar; Syed Hissar; Akshat Jain; Ranjana Gondal; Shiv Kumar Sarin (Wolters Kluwer Medknow Publications, 2011)
Background and Aims: Hepatic steatosis (HS) is highly prevalent in chronic hepatitis C and is an important variable predicting progression of histological injury, insulin resistance, and reduced response to antiviral therapy. There are limited data on HS in patients with chronic hepatitis B (CHB). This is relevant since response to current antiviral therapies for CHB is rather limited. We investigated the spectrum and predictors of HS in CHB patients. Materials and Methods: Liver biopsies of consecutive patients of chronic Hepatitis B Virus (HBV) infection were studied and were categorized as: Group I - hepatosteatosis (>5%) and Group II - no steatosis (£5%). Anthropometric, histological, biochemical, virological, and metabolic determinants were compared. Logistic regression analysis was applied to identify variables that were independently associated with the presence of steatosis. Results: Of the 350 patients, 118 (33.7%) liver biopsies showed steatosis (Group I); 65 (55.1%) had mild (6 to <25%) and 53 (44.9%) had moderate to severe steatosis (325%). Patients in group I, compared with group II, were older (35.5 ± 10.5 vs 27.9 ± 14.0 years, P < 0.01), predominantly male (M: F, 10.8: 1 vs 4.8: 1, P = 0.035), obese (75.0% vs 23.4%, P < 0.01), with higher body mass index (25.2 ± 4.8 vs 20.4 ± 3.5, P < 0.01), with higher triglycerides (138.8 ± 62.1 vs 88.0 ± 27.9, P = 0.02), with higher cholesterol (171.9 ± 43.5 vs 139.3 ± 37.6, P = 0.017), and with higher serum insulin (13.1 ± 9.1 vs 9.1 ± 6.0, P < .027) levels. HBV DNA level was significantly lower in group I than group II; however, HBV genotype did not influence HS. By multivariate regression analysis, only high serum triglyceride level was independent parameter associated with HS. Conclusions: Steatosis is seen in one-third cases with HBV-related chronic liver disease and is associated with host metabolic factors, especially serum triglyceride levels, whereas HBV DNA level negatively correlated with HS.